Fig. 2 in Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica - Kuzmina, T. A.; Salganskiy, O. O.; Vishnyakova, K. O.; Ivanchikova, J.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2022)
Fig. 2. Proportion (%) of helminth species parasitizing three teleost fishes from the South Orkney Islands area, West Antarctica on larval and adult stages. Published as part of Kuzmina, T. A., Salganskiy, O. O., Vishnyakova, K. O., Ivanchikova, J., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2022, Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica, pp. 135-152 in Zoodiversity 56 (2) on page 144, DOI:10.15407/zoo2022.02.135, http://zenodo.org/record/7175665